2022
DOI: 10.1186/s10195-022-00666-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of two novel devices for epiphysiodesis in the reduction of excessive predicted final height in tall stature

Abstract: Background: In the treatment of tall stature, the reduction of excessive predicted final height can either be achieved by hormonal treatment or surgically by temporary (tED) or permanent (pED) epiphysiodesis. The present study evaluates the preliminary results of two novel devices for tED and pED around the knee to reduce the predicted final height. Materials and methods:A retrospective analysis was performed to evaluate the clinical and radiographic outcome after bilateral epiphysiodesis for the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several other studies have assessed the relationship between the femoral notch-intercondylar distance and stability of the anterior cruciate ligament [26,27,[30][31][32]. Iriuchishima et al observed a higher incidence of ante- physiodesis around the knee for correction of LLD or hemi-epiphysiodesis of the distal femur or proximal tibia for correction of angular deformities [5,9,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have assessed the relationship between the femoral notch-intercondylar distance and stability of the anterior cruciate ligament [26,27,[30][31][32]. Iriuchishima et al observed a higher incidence of ante- physiodesis around the knee for correction of LLD or hemi-epiphysiodesis of the distal femur or proximal tibia for correction of angular deformities [5,9,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Definitive epiphysiodesis seems to be combined with a lesser risk for secondary angular deformity. 4 Treatment of LLD with either tension band plating (TBP) or transphyseal screws has been further investigated. TBP may have a greater risk of complications in temporary epiphysiodesis in comparison with the use of transphyseal screws.…”
Section: Guided Growthmentioning
confidence: 99%